Differential default mode network trajectories in asymptomatic individuals at risk for Alzheimer's disease - Bokde, Arun; Chiesa, Patrizia A.; Cavedo, Enrica; Vergallo, Andrea; Lista, Simone; Potier, Marie-Claude; Habert, Marie-Odile; Dubois, Bruno; Thiebaut de Schotten, Michel; Hampel, Harald; the INSIGHT-preAD study group; the Alzheimer Precision Medicine Intitiative (APMI) (My University, 2019)
Introduction: The longitudinal trajectories of functional brain dynamics and the impact of genetic risk factors in individuals at risk for Alzheimer's disease are poorly understood. Methods: In a large-scale monocentric cohort of 224 amyloid stratified individuals at risk for Alzheimer's disease, default mode network (DMN) resting state functional connectivity (FC) was investigated between two serial time points across 2 years. Results: Widespread DMN FC changes were shown in frontal and posterior areas, as well as in the right hippocampus. There were no cross-sectional differences, however, apolipoprotein E ε4 (APOE ε4) carriers demonstrated slower increase in FC in frontal lobes. There was no impact of individual brain amyloid load status. Discussion: For the first time, we demonstrated that the pleiotropic biological effect of the APOE ε4 allele impacts the dynamic trajectory of the DMN during aging. Dynamic functional biomarkers may become useful surrogate outcomes for the development of preclinical targeted therapeutic interventions.
Keywords: Brain functional dynamics; Precision medicine; fMRI; Alzheimer's disease; Subjective memory complaints